If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 1 + -6k + -6k Combine like terms: -6k + -6k = -12k 13 = 1 + -12k Solving 13 = 1 + -12k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '12k' to each side of the equation. 13 + 12k = 1 + -12k + 12k Combine like terms: -12k + 12k = 0 13 + 12k = 1 + 0 13 + 12k = 1 Add '-13' to each side of the equation. 13 + -13 + 12k = 1 + -13 Combine like terms: 13 + -13 = 0 0 + 12k = 1 + -13 12k = 1 + -13 Combine like terms: 1 + -13 = -12 12k = -12 Divide each side by '12'. k = -1 Simplifying k = -1
| 13x+24=16x+6 | | x^2+9x-224=0 | | 5xy*-4x= | | X=4y+30 | | (x^2+2x-3)*(x^2+3x-4)= | | -v-5c=6 | | 4-(f-2)=4 | | (x^2+2x-3)-(x^2+3x-4)= | | 3x+6(25-x)=12 | | 3.26u-7.22u-0.29=2.77 | | 6(4+y)-y=4(6+y)+y | | 7y+2(y-6)=3(y+2)-5 | | -21=-9+4(x-8) | | =4x^2+5x-6 | | b+3/2b+(b+45)+(2b+90)+90=0 | | 0.12(y-6)+0.06y=0.8y-0.70 | | 20x+4=64 | | 2x^2-147x+49=0 | | x+5+x=-3 | | 1=-3r+2r | | 2x+3+3x=x+3 | | 5(3y-1)-4y=6 | | 2y+y+32=20 | | -17/20+19/28 | | 2x+30=46 | | 2y+5y+7+5y+15+3y= | | 1/15y+3/10=11/10 | | 5x^3-20x+2=y | | -4x=-(18) | | 2x-1=2x-12 | | 3/8+1/20 | | x^2+10x+29= |